Vivre l'histoire : recit biographique et filiation – le cas de Jean Rouaud - Katarzyna Thiel-Jańczuk (Études romanes de Brno, 2013)
The present paper analyses a possibility of literary expression of historical past which is not known by a narrator from his own experience but only through his ancestors' – direct participants of traumatic events – accounts. On the basis of Michel de Certeau's and Paul Ricœur's theoretical reflections referring to the status of contemporary historical and fictional story and its narration and the intimate versus the official mode of biographical storytelling, the author of the text attributes these two modes to heroic, traditional type of biographical narration and the currently widespread filiative story (recit de filiation) respectively. The article discusses the process of confiding one's memories of the past in a series of stories, also called a "family autobiography" by a French writer, Jean Rouaud. In this process, a particular role is played by "corporeal memory" which is a way of transmitting physical suffering from one generation to another. Literature, which allows for such a transmission, becomes thus an unofficial, "minor" form of a historiographic discourse.